P32 When a test is neither positive nor negative: the impact of equivocal and indeterminate quantiferon TB IGRA in a UK population. (14th November 2013) - Saunders, P; Reading, J; Harvey, J; Murthy, S; Capocci, S; Hopkins, S; Seneviratne, S; Cropley, I; Lipman, M
Abstract : Introduction: For the diagnosis of latent tuberculosis (LTBI), clinicians like interferon-gamma based assays (IGRA) to be either positive or negative. Tests can be indeterminate (failure of the positive or negative control); and recently an equivocal category has been introduced for QuantiFERON IGRA results that lie around the positive cut off, 0.35 IU/mL, covering the range 0.2–0.7 IU/mL. Within our hospital, it is recommended that indeterminate or equivocal results are initially repeated by the requesting clinician. We report our outcomes from March 2010, when the equivocal category was introduced. Methods: Hospital pathology and clinical records were data-mined. Cost analysis used local NHS costs. Results: Tests for 1964 individuals were processed (over one-third from Occupational Health, and another one-third pre-biological therapy). 92% of subjects had a definitive first result, with 6% (116) equivocal and 2% (42) indeterminate (Table 1 ). 60% of equivocal tests were below the positive cut off of 0.35. The demographics of those with an equivocal result were broadly comparable with the whole tested population. Almost half of the equivocal tests were not repeated (Table 1 ). 45% of repeats were negative and one-third still equivocal. 12 of 34 subjects referred to the TB service were treated for LTBI–10 with a positive IGRA on re-testing. One other patient with an initial equivocal test developed active TB during follow up. 43% of people with an indeterminate result had no repeat test (Table 1 ). 1 of 6 subjects referred to the TB service following an indeterminate IGRA received LTBI treatment. Cost-analysis indicated that equivocal and indeterminate results plus subsequent TB service management increased the cost of each initial QuantiFERON diagnostic test from £35 to £40.76 per patient. Conclusion: 8% of subjects had an equivocal or indeterminate first IGRA result. The recommended subsequent action often was not followed by the requesting clinicians. When repeated, the test provided a definitive result in two-thirds of subjects - the majority being negative. This adds an appreciable cost to the test, and brings it in line with other commercial IGRA. Further education of referring clinicians is required to minimise avoidable waste and optimise patient care.